2016
DOI: 10.1007/s00415-016-8174-4
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of functional and structural connectivity of freezing of gait in Parkinson’s disease

Abstract: This study assessed the patterns of functional and structural connectivity abnormalities in patients with Parkinson's disease with freezing of gait (PD FOG+) compared with those without freezing (PD FOG-) and healthy controls (HCs). Resting state functional MRI (rs-fMRI) and diffusion tensor imaging (DTI) scans were obtained from 14 PD FOG+, 16 PD FOG- and 16HCs. Between-group difference in pedunculopontine nucleus (PPN) functional connectivity (FC) was performed to assess FC dysfunction. Tract-based spatial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
110
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 61 publications
16
110
1
1
Order By: Relevance
“…In PD this includes degeneration of cholinergic (Rinne et al, 2008; Karachi et al, 2010; Pienaar et al, 2013), GABAergic and glycinergic cells (Pienaar et al, 2013). Neuroimaging indicates that locomotor deficits in PD patients are associated with additional MLR abnormalities (notably in the PPN), including altered connectivity between the MLR, thalamus, and motor cortical regions (Fling et al, 2013, 2014), abnormal microstructure (Vercruysse et al, 2015; Youn et al, 2015; Wang et al, 2016), atrophy of the MLR gray matter (Snijders et al, 2011; Fioravanti et al, 2015) and abnormal metabolic activity following a walking task (Tard et al, 2015). Additionally, anatomopathological studies revealed the presence in the MLR of alpha-synuclein immuno-reactive Lewy Bodies (e.g., Seidel et al, 2015), and mitochondrial abnormalities (Pienaar et al, 2013) in PD.…”
Section: Possible Role Of the Descending Dopaminergic Pathway In Pdmentioning
confidence: 99%
“…In PD this includes degeneration of cholinergic (Rinne et al, 2008; Karachi et al, 2010; Pienaar et al, 2013), GABAergic and glycinergic cells (Pienaar et al, 2013). Neuroimaging indicates that locomotor deficits in PD patients are associated with additional MLR abnormalities (notably in the PPN), including altered connectivity between the MLR, thalamus, and motor cortical regions (Fling et al, 2013, 2014), abnormal microstructure (Vercruysse et al, 2015; Youn et al, 2015; Wang et al, 2016), atrophy of the MLR gray matter (Snijders et al, 2011; Fioravanti et al, 2015) and abnormal metabolic activity following a walking task (Tard et al, 2015). Additionally, anatomopathological studies revealed the presence in the MLR of alpha-synuclein immuno-reactive Lewy Bodies (e.g., Seidel et al, 2015), and mitochondrial abnormalities (Pienaar et al, 2013) in PD.…”
Section: Possible Role Of the Descending Dopaminergic Pathway In Pdmentioning
confidence: 99%
“…Clinical symptoms involve impairment of diverse motor and non-motor symptoms that get progressively worse over time. The decline in clinical performance has been associated with changes in morphological properties of structural and functional neuroimaging networks (Lucas-Jiménez et al 2016; Wang et al 2016; de Schipper et al 2017). In turn, studies have investigated the relationship between these imaging networks and genetic variants in PD-related genes to provide new insights into the pathogenesis of PD (van der Vegt et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that NFOG‐Q scores did not differ significantly between time points as such and that no systematic decrease or increase of scores was found across the cohorts suggests that becoming more aware of freezing behavior could go in both directions, that is, more or less positive assessments of FOG. Several studies reported recall bias as a limitation in the previous freezing of gait questionnaire (FOG‐Q) or other clinical scales . As a result, one study even used the second assessment of the FOG‐Q instead of the first to compensate for this issue .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported recall bias as a limitation in the previous freezing of gait questionnaire (FOG-Q) or other clinical scales. [36][37][38] As a result, one study even used the second assessment of the FOG-Q instead of the first to compensate for this issue. 39 To help the accuracy of retrospective assessment of FOG, the NFOG-Q is accompanied by exemplary videos of FOG to serve as a reference before it is completed.…”
Section: Discussionmentioning
confidence: 99%